One-carbon metabolites, B vitamins and associations with systemic inflammation and angiogenesis biomarkers among colorectal cancer patients: results from the ColoCare Study - Kiblawi, Rama; Gigić, Biljana; Schrotz-King, Petra; Habermann, Nina; Schneider, Martin; Ulrich, Alexis (British journal of nutrition, 2020)
B vitamins involved in one-carbon metabolism have been implicated in the development of inflammation- and angiogenesis-related chronic diseases, such as colorectal cancer (CRC). Yet, the role of one-carbon metabolism in inflammation and angiogenesis among CRC patients remains unclear. The objective of this study was to investigate associations of components of one-carbon metabolism with inflammation and angiogenesis biomarkers among newly diagnosed CRC patients (n 238) in the prospective ColoCare Study, Heidelberg. We cross-sectionally analysed associations between twelve B vitamins and one-carbon metabolites and ten inflammation and angiogenesis biomarkers from pre-surgery serum samples using multivariable linear regression models. We further explored associations among novel biomarkers in these pathways with Spearman partial correlation analyses. We hypothesised that pyridoxal-5’-phosphate (PLP) is inversely associated with inflammatory biomarkers. We observed that PLP was inversely associated with C-reactive protein (CRP) (r -0·33, Plinear < 0·0001), serum amyloid A (SAA) (r -0·23, Plinear = 0·003), IL-6 (r -0·39, Plinear < 0·0001), IL-8 (r -0·20, Plinear = 0·02) and TNFα (r -0·12, Plinear = 0·045). Similar findings were observed for 5-methyl-tetrahydrofolate and CRP (r -0·14), SAA (r -0·14) and TNFα (r -0·15) among CRC patients. Folate catabolite acetyl-para-aminobenzoylglutamic acid (pABG) was positively correlated with IL-6 (r 0·27, Plinear < 0·0001), and pABG was positively correlated with IL-8 (r 0·21, Plinear < 0·0001), indicating higher folate utilisation during inflammation. Our data support the hypothesis of inverse associations between PLP and inflammatory biomarkers among CRC patients. A better understanding of the role and inter-relation of PLP and other one-carbon metabolites with inflammatory processes among colorectal carcinogenesis and prognosis could identify targets for future dietary guidance for CRC patients.
Gesehen am 03.07.2020